From Knowledge to Application: Effects of Performance Feedback and Goal-Setting on Pre-Service Teacher Implementation of Evidence-Based Practice - Criss, Caitlin J.; Devine, Stephanie M.; Massey, Cynthia C. (Journal of the American Academy of Special Education Professionals, 2024)
Teacher implementation of evidence-based practices (EBPs) is critical for student success, yet a gap remains between research to practice. Two EBPs that specifically promote student engagement and positive behavior are specific praise (BSP) and active student responding (OTR). Unfortunately, many classroom teachers, specifically pre-service teachers, struggle with implementing EBPs. While the caseload demands continue to increase for university field supervisors, educator preparation programs are tasked with finding effective and efficient ways to provide feedback to pre-service teachers. The purpose of this study was to evaluate the effectiveness of written performance feedback and goal setting on increasing evidence-based classroom management practices with special education pre-service teachers. Using a single-case multiple probe design, researchers found that all pre-service teachers increased their rate of BSP and OTR after receiving performance feedback with and without goal setting by email. Results from social validity, limitations, and directions for future research are also discussed.